Dopuszczalność „złotej akcji” w polskim systemie prawa spółek - Piotrowski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The present article is devoted to admissibility of the “golden share” in Polish stock company. The current legislation does not explicitly allow or prohibit the existence of this statutory instrument. The article considered the possibility of granting such special privileges both as a shareholding privilege and as a personal right granted to a shareholder. The admissibility of these concepts has been assessed on the basis of the rules and common rules of company law, as well as the concepts incompatible with them has been criticised. In addition, the issue of statutory “gold shares” of the State Treasury, which grants the relevant minister a right to object to the specific decisions of the company, is outlined. Regulations and concepts under the current and previous law has been compared, as well as the above solutions were compared with the general rules and principles of company law.
Keywords: golden share; company law; State Treasury; legislation; stock company; statutory instrument; shareholder; personal right; shareholding privilege